A inclusão de alunos com transtorno do espectro do autismo na perspectiva de seus professores: estudo de caso em quatro escolas do município de Santa Maria/RS - Kubaski, Cristiane (2014)
This paper investigates the school educational inclusion of children with Autistic Spectrum Disorder (ASD) in Santa Maria, RS. Thus, the inclusion will be analyzed in a more comprehensive way, including four referring axes: presence, participation, acceptance and apprenticeship of students with ASD. The research has qualitative character, being carried out from exploratory multiple case. The objective is to describe how the inclusion of students with ASD in mainstream schools in Santa Maria is working from the perspectives of their teachers in this context. For that, four teachers of first years of elementary school, who teach students diagnosed with ASD by Educacenso 2012, took part in this research. It is noteworthy that the findings of this study point to the fact that the strategies used by the teachers seem to favor the inclusion of students with ASD in mainstream schools. However, there are still barriers to participation and learning of these students who constitute a challenge to the inclusive process. Furthermore, it is suggested that the inclusion is investigated in a broader sense, considering besides the presence of the student at school, how he is participating, interacting, learning and being perceived in the inclusive setting.